Tailored use of belatacept in adolescent kidney transplantation. Issue 3 (16th October 2019) - Blew, Kathryn H.; Chua, Annabelle; Foreman, John; Gbadegesin, Rasheed; Jackson, Annette; Nagaraj, Shashi; Sadun, Rebecca; Wigfall, Del; Kirk, Allan D.; Chambers, Eileen T.
Abstract : Adolescent transplant recipients are at risk for nonadherence, development of de novo donor‐specific antibody ( dn DSA), and allograft loss. Belatacept, a selective T cell costimulatory blocker, is associated with reduced dn DSA, improved renal function, and prolonged allograft survival when compared to calcineurin inhibitor‐based regimens in adults; however, its use in children is scant. Three adolescents were initiated on belatacept between August 2017 and September 2018 at the time of kidney transplantation. Selection criteria included age ≥ 14 and EBV IgG + serostatus. Intraoperative alemtuzumab and methylprednisolone were given as induction therapy. Tailored maintenance therapy included steroid‐free belatacept and sirolimus for two patients. One patient was initially maintained steroid‐free on belatacept and belimumab, an inhibitor of B cell activating factor to treat concurrent systemic lupus erythematous; steroids were added subsequently. Renal function, biopsy‐proven rejection, dn DSA, allograft survival, infection, nonadherence, and proteinuria were monitored. Renal function was 86, 73, 52 mL/min/1.73 m 2 at 20, 20, and 8 months, respectively. There was 100% adherence to therapy and no development of dn DSA. All patients had treatable infections. One developed steroid‐responsive acute cellular rejection. Belatacept‐based regimens can be tailored for adolescent recipients with good short‐term clinical outcomes. Abstract : The de novo use of belatacept provides safe and efficacious immunosuppression with good short‐term clinical outcomes in adolescent kidney transplant recipients.